2017
DOI: 10.1080/14397595.2017.1332474
|View full text |Cite
|
Sign up to set email alerts
|

Difficulty in the diagnosis of bone and joint pain associated with pediatric acute leukemia; comparison with juvenile idiopathic arthritis

Abstract: Leukemia-associated osteoarthralgia is often indistinguishable from rheumatic diseases by imaging and laboratory findings and should be confirmed by bone marrow examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…Bone disease: osteofibrous disease, osteoid osteoma [94][95][96][97][98]. Neoplastic: Langerhans cell histiocytoma, leukemia-associated osteoarthralgia, sarcoma [99,100]. Osteonecrosis: 15-47% of pediatric patients after high-dose glucocorticoids.…”
Section: Pathogenic Bme In Childrenmentioning
confidence: 99%
“…Bone disease: osteofibrous disease, osteoid osteoma [94][95][96][97][98]. Neoplastic: Langerhans cell histiocytoma, leukemia-associated osteoarthralgia, sarcoma [99,100]. Osteonecrosis: 15-47% of pediatric patients after high-dose glucocorticoids.…”
Section: Pathogenic Bme In Childrenmentioning
confidence: 99%
“…Apart from the characteristic symptoms of fever, pallor, bleeding tendency, hepatomegaly, and splenomegaly, there are a number of unusual clinical manifestations including musculoskeletal (MSK) symptoms [ 3 ]. MSK involvement has been reported in childhood leukemia at rates varying from 7.1 to 62.3% [ 4 12 ]. In 2016, a systematic review and meta-analysis reported that MSK symptoms were a prominent clinical presenting feature in childhood leukemia, including limb pain (43%), bone pain (26%), joint pain (15%), and limping (11%) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in some studies, MSK involvement was found to be more frequent in acute lymphoblastic leukemia (ALL), especially B-cell ALL, than acute myeloid leukemia (AML) [ 13 – 15 ]. This subgroup with MSK involvement also had lower rates of hematologic abnormalities, as well as peripheral blast counts at initial presentation [ 12 16 ]. Therefore, childhood leukemia with MSK involvement can mimic rheumatic or orthopedic conditions and lead to delayed diagnosis of leukemia [ 14 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, bone pain or radiographic abnormalities can be very frequent at presentation in cases of acute lymphoblastic leukemia (ALL) [3]. On the other hand, bone involvement on initial presentation is extremely rare in AML, and only six such cases have been reported in patients below the age of 15 years (Table 1) [4][5][6][7][8]. Bone pain in AL is caused by the proliferation of leukemic cells in the bone marrow and pressure effects within the medullary canal and under the periosteum [9].…”
Section: Discussionmentioning
confidence: 99%